The Relative Age Effect based on playing-position and performance on Brazilian elite men’s basketball - de Oliveira Castro, Henrique; de Oliveira, Vivian [UNESP]; de Souza Rocha, Matheus; de Souza, Walber Figueiredo; De Castro Ribeiro, Lucas; Gomes, Sérgio Adriano; Figueiredo, Lucas Savassi (Servicio de Publicaciones de la Universidad de Murcia, 2024)
The aim of this study was to verify the existence of RAE in Brazilian elite male basketball, considering athletes’ birth quartiles, playing positions, team placement, and tactical-technical performance in the Novo Basquete Brasil (NBB). A total of 454 male athletes were analyzed according to their birth quartiles, playing positions, final team placement in the championship, and tactical-technical performance. The goodness of fit chi-square test was used to compare the distribution of birth quartiles for the overall sample and based on playing positions and team final placements. The Kruskal-Wallis test was used to compare tactical-technical performance based on birth quartiles. Results indicated that athletes born in the last quartile of the year were less frequent than those born in the first (p < 0.001), second (p < 0.006), and third (p < 0.001) quartiles of the year for the overall sample. Unequal distributions were also reported for the Small Forward position (p = 0.018). Regarding the final team placements, unequal distributions were observed for intermediate teams in the 2019/2020 season (p = 0.014), top teams in the 2020/2021 season (0.027), and bottom teams in the 2021/2022 season (p = 0.005). No association was found between RAE and any tactical-technical performance variable (p > 0.005). It is concluded that RAE was present in the NBB in Brazilian elite male athletes, but it does not seem to be a factor associated with collective nor individual tactical-technical performance.
El Efecto de la Edad Relativa basado en la posición de juego y el rendimiento en el baloncesto de élite masculino brasileño
O Efeito da Idade Relativa baseado na posição de jogo e desempenho no basquetebol masculino Brasileiro de elite
Keywords: Athlete Developement; Baloncesto; Basketball; Basquetebol; Birth quartile; Cuartil de Nacimiento; Desarrollo del Atleta; Desempenho tático-técnico; Desenvolvimento de atletas; Efecto de la Edad Relativa; Efeito da Idade Relativa; Quartis de nascimento; Relative Age Effect; Rendimiento Táctico-Técnico; Tactical-Technical Performance